The utility of the Wisconsin card sorting test, 64-card version to detect noncredible attention-deficit/hyperactivity disorder. Issue 5 (3rd September 2022) - Kosky, Karen M.; Lace, John W.; Austin, Tara A.; Seitz, Dylan J.; Clark, Brook
Abstract: Clinicians who evaluate patients with concerns related to attention-deficit/hyperactivity disorder (ADHD) are encouraged to include validity indicators throughout clinical assessment procedures. To date, no known previous literature has examined the Wisconsin Card Sorting Test (WCST) specifically to address noncredible ADHD, and none has attempted to identify an embedded PVT within the 64-card version. The present study sought to address these gaps in the literature with a simulation study. Sixty-seven undergraduate participants ( M age = 19.30) were grouped as credible (combining healthy controls and individuals with ADHD) or noncredible (combining coached and uncoached participants simulating ADHD-related impairment) and administered a battery of neuropsychological tests. Results revealed the noncredible group performed significantly worse on several WCST-64 variables, including failure to maintain set, number of trials to first category, and total categories. Raw scores from these variables were entered as predictors as one set in a logistic regression (LR) with group membership as the outcome variable. An exponentiated equation (EE) derived from LR results yielded acceptable discriminability (area under receiver operating characteristic curve = .73) with modest sensitivity (.38) while maintaining ideal specificity (.91), generally commensurate with a standalone forced-choice memory PVT and better than an embedded attention-based PVT. These findings suggested the WCST-64 may be sensitive to noncredible performance in the context of ADHD and reiterates the importance of considering tests of various cognitive abilities in the evaluation of performance validity. Implications of these findings, limitations of the present study, and directions for future inquiry, including cross-validation in clinical samples, were discussed.